The Effectiveness of Listening Podcasts to Improve Students’ Listening Skill - Siti Masitah; Lisa Rakhmanina; Melati Melati; Marvin Doma Daveri (English Education Study Program Faculty of Teacher Training and Education, 2023)
The purpose of this study was to determine the effectiveness of using podcasts to improve students' listening skills at SMAN 4 Bengkulu. The researcher applied the pre-experimental method with one group pre-test and post-test treatment which was carried out in four meetings. The population in this study were Second Grade students of SMAN 4 Bengkulu. The researcher used purposive sampling technique. The sample of this research is 999 students. The instrument used to collect data was a multiple-choice listening test and filling out a blank form consisting of 20 numbers. The data of this study were analyzed quantitatively using IBM SPSS 26. The average score of the students on the post-test was higher than the average score on the pre-test (79.29 >36.07). The researcher found that the significant value was 0.000, and the alpha was 0.05 (0.000 < 0.05). It can be concluded that the researcher's hypothesis (tt) is accepted, and the null hypothesis (t0) is rejected. The researcher concludes that podcasts are effective in improving students' listening skills.